MEASURING THE EFFECTIVITY OF ENVIRONMENTAL LAW;LEGAL INDICATORS FOR SUSTAINABLE DEVELOPMENT (PETER LANG, 2021)
This book presents a new method for measuring the effectivity of national and international environmental law. It took four years of research and experimentation to develop a way to construct evidence-based legal indicators. The existing environmental indicators evaluate only statistical, scientific or economic data. With legal indicators, governments, parliaments and other public and private actors, including environmental NGOs, will be able to assess accurately and concretely, on a scientific basis, what the gaps, progress and setbacks in the implementation of international conventions and national laws are. The legal indicators will also serve as innovative tools for decision-making, in particular to carry out legislative reforms in full knowledge of the facts and not blindly, as well as to avoid regressions in environmental law. The mathematical method used makes it possible, through a questi onnaire addressing all the legal and institutional stages of the application of legal texts, to provide data highlighting both the points to be improved and the strengths of the application of the law. This essay is an update of a first book published in 2018 by the Institut de la Francophonie pour le développement durable. It is the result of a partnership between the International Centre for Comparative Environmental Law and the Normandy Chair for Peace.
Keywords: Environmental law -- Research.; Sustainable development -- Law and legislation.; Environmental law -- Research; Sustainable development -- Law and legislation